A threshold of β-CTX (0.3 ng/mL) with low estradiol identifies high-risk perimenopausal women for bone loss: a cross-sectional study - Feng, Xufen; Xiao, Wenjun; Zhang, Rongshan (Frontiers in Endocrinology, 2025)
BackgroundIncreasing evidence has demonstrated accelerated bone loss during perimenopause. The detection of bone loss relies heavily on dual-energy X-ray absorptiometry (DXA). However, DXA is not sensitive enough for early bone loss. Therefore, an easy and sensitive method is urgently needed for identifying high-risk women before irreversible bone loss occurs.ObjectiveTo 1) define a clinically meaningful β-CTX threshold (≥ 0.3 ng/mL) for perimenopausal bone loss prediction, 2) assess the predictive value of E2 and β-CTX, both individually and in combination, for bone loss in perimenopausal women.MethodsOne hundred and thirty female participants met the inclusion/exclusion criteria were enrolled in this study from March 2024 to March 2025. Enrolled subjects underwent DXA examination and blood tests, including measurements of E2, β-CTX, TP1NP, D3, and IGF-1. The correlations between E2, β-CTX, TP1NP, D3, IGF-1 and T-scores were performed using Spearman correlation analysis. The predicting value of E2, β-CTX and combination for perimenopausal bone loss were studied by ROC curve analysis.ResultsThere were significant correlations between E2, β-CTX, TP1NP and T-scores, but not between D3, IGF-1 and T-scores. The threshold value of E2 alone in predicting perimenopausal bone loss was 62.7 pmol/L. Its sensitivity and specificity were 79.1% and 93.2%, respectively. The threshold value of β-CTX alone in predicting perimenopausal bone loss was 0.30 ng/mL. Its sensitivity and specificity were 79.3% and 96.4%, respectively. The ROC curve of E2 combined with β-CTX showed that the AUC was 0.950. Its sensitivity and specificity were 88.4% and 97.7%, respectively, which were higher than that in E2 and β-CTX alone.ConclusionA clinically meaningful β-CTX threshold (≥ 0.3 ng/mL) was defined for perimenopausal bone loss prediction, and the combination of E2 and β-CTX is a simple and reliable method for predicting perimenopausal bone loss, with high sensitivity and specificity. A threshold of β-CTX (0.3 ng/mL) with low estradiol identifies high-risk perimenopausal women for bone loss.